Liquid-based endometrial cytology associated with curettage in the investigation of endometrial carcinoma in postmenopausal women - Ke Ma; Xi Yang; Rui Chen; Jian Zhao; Ying Dong; Nai-Yi Zhang; Xiu-Hua Ma; Qin-Ping Liao (Taiwanese Journal of Obstetrics & Gynecology, 2016)
Objective: The aim of this study was to investigate the diagnostic accuracy of liquid-based endometrial cytology in postmenopausal women, in comparison with histology. Materials and methods: There were 790 postmenopausal women scheduled for hysteroscopy enrolled in this study. After providing informed consent, all patients proceeded sequentially through endometrial cytology, hysteroscopy, and then dilatation and curettage (D&C). Cytology sampling was performed by brushing the uterus cavity using SAP-1 and the sample was prepared to liquid-based smear using SurePath technology. The slides were stained by Papanicolaou method. All cytological diagnoses were correlated with the D&C histological diagnoses. Results: Cytohistological correlations were possible in 567 (71.8%) patients: the D&C was inadequate in 204 (25.8%) patients; the cytology was inadequate in 32 (4.1%) patients; and both were inadequate in 13 (1.6%) patients. SAP-1 provided more sufficient material for cytology than D&C can for histology (p < 0.001). Taking atypical hyperplasia and endometrial carcinoma as a positive result, the diagnostic accuracy of liquid-based endometrial cytology was 81.5%; sensitivity was estimated at 75.9%, specificity at 83.3%, positive predictive value at 59.1% and negative predictive value at 91.6%. Conclusion: Liquid-based endometrial cytology can be considered a useful method in the detection of endometrial pathology in postmenopausal women.